Public Information Disclosure Increases Transparency and Accountability of Sumedang Regency Government - Linda Wianti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this study was to determine the extent of the implementation of the policy of Law Number 14 of 2008 concerning Public Information Disclosure. The research method used is a qualitative research method. Data collection techniques are carried out through library research and field studies which include: Observation, Interviews, Documentation Studies, and Triangulation. Determination of samples/informants in this study was carried out using purposive sampling and further analysis of data from the Miles and Huberman model, namely: data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that there are several factors that support the implementation of the policy of Law Number 14 of 2008 concerning Public Information Disclosure to increase employee awareness of their obligations. In implementing the policy of Law Number 14 of 2008 concerning Public Information Disclosure at the Communication and Informatics Service, overall the coding and statistics of Sumedang Regency can be said to be quite good. However, there are several obstacles, namely the lack of supporting resources (employees) in conducting socialization, lack of understanding from the community or not knowing at all about the policy and lack of employee understanding of the Law Policy on public information disclosure. Efforts to overcome these obstacles include increasing supporting resources (employees), conducting socialization during surveys, increasing participation and increasing employee awareness to be responsible for their duties by conducting periodic evaluations.